1998
DOI: 10.1021/la9710177
|View full text |Cite
|
Sign up to set email alerts
|

Directing Oleate Stabilized Nanosized Silver Colloids into Organic Phases

Abstract: Nanosized hydrophobic, oleate stabilized silver organosols in various organic solvents are obtained using a solvent exchange method. The silver particles are initially prepared as a hydrosol in the presence of sodium oleate (surfactant). Then a transfer of the colloid to an organic phase is induced by a low concentration of several agents such as orthophosphoric acid, with a transfer efficiency of 50−70%. The hydrophobic colloid is stable and the particles retain their integrity even after the solvent is evapo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
232
0
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 265 publications
(247 citation statements)
references
References 85 publications
13
232
0
2
Order By: Relevance
“…It was concluded that Ag + ions coordinated to the relatively free -COOH groups, then Ag nanoparticles formed on the surface of the TiO 2 particles with the oleic acid acting as a linker between the titania and Ag nanoparticles. These conclusions are in agreement with previous reports, since oleic acid is a well-known capping agent for Ag nanoparticles [44][45][46]. Figure 5B showed a main peak at 531.2 eV which was identified as O from alumina.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…It was concluded that Ag + ions coordinated to the relatively free -COOH groups, then Ag nanoparticles formed on the surface of the TiO 2 particles with the oleic acid acting as a linker between the titania and Ag nanoparticles. These conclusions are in agreement with previous reports, since oleic acid is a well-known capping agent for Ag nanoparticles [44][45][46]. Figure 5B showed a main peak at 531.2 eV which was identified as O from alumina.…”
Section: Resultssupporting
confidence: 93%
“…Moreover, in addition to shifting the pH to 9.26, the Ag + ions were reduced due to addition of NaBH 4 . Thus it could be concluded that oleic acid coordinated with the Ag nanoparticles through its head groups, as oleic acid is a well-known capping agent for Ag nanoparticles [44][45][46]. No significant shift was observed in the region 3010-2850 cm -1 throughout the synthesis (cf.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…This technique is based upon the electrostatic interaction between oppositely charged species from dilute solution [36][37][38]. Nanocomposite materials which are based on inorganic nanoparticles and polymers offer unique properties, such as, optical, magnetic, catalytic, thermal and electrochemical, which depend on particle size, shape, dimensions and surrounding environment [39][40][41][42][43]. The unusual properties of metallic nanoparticles are due to the collection of high energy surface atoms compared to the bulk solid material.…”
Section: Introductionmentioning
confidence: 99%